On the status of some species of Braconidae (Hymenoptera) described by J. C. Fabricius and the synonymy of Dichelosus Szépligeti with Coccygidium De Saussure - M., Carlos E. Sarmiento; Sharkey, Michael (Zootaxa, 2005)
The status of five species of Braconidae described by Fabricius is changed. Lectotypes are designated for all five. Ichneumon hospitator, Bracon anator, and Ophion pennator are transferred to the genus Coccygidium combs. nov. Ichneumon ornator is transferred to Coccygidium and considered a junior synonym of C. hospitator comb. and syn. nov. Bracon similator is transferred to the genus Hemibracon comb. nov. Dichelosus fuscipennis is considered a junior synonym of C. hospitator syn. nov. The genus Dichelosus is synonymized with Coccygidium syn. nov., and the member species are all transferred to Coccygidium: C. fuscipennis comb. nov., C. peruensis comb. nov., C. brasiliensis comb. nov., C. dubiosus comb. nov., C. similis comb. nov., C. variegatus comb. nov., and C. demerarus comb. nov.